The Correlation of Maternal Age and the Incidence of Preeclampsia at Aura Syifa Hospital - Anggita Retno Sari; Ira Titisari; Eny Sendra (STIKes Patria Husada Blitar, 2021)
Preeclampsia is a condition when hypertension and proteinuria occurs after 20 weeks of pregnancy. The exact cause of preeclampsia is currently unknown, but many factors influence the occurrence of preeclampsia, especially the age factor. This study was aimed to determine the correlation between maternal age and the incidence of preeclampsia. This study was analytical survey designed with retrospective study method. From Aura Syifa hospital, 142 medical records in of pregnant women in 2017 were taken 105 samples by using simple random sampling technique. The result of this study indicated that delivered mothers who were in reproductive age (20-35 years old), 25.8% of them had preeclampsia and 31,1% had severe preeclampsia. The data analyzed by suing chi-square correlation and the result was Ï (0.00) < Î± (0.05) which meant that there was a correlation between maternal age and the incidence of preeclampsia. It would be better for couples planning pregnancy in healthy reproductive age for minimize the risk of preeclampsia.